2016
DOI: 10.1038/srep24472
|View full text |Cite
|
Sign up to set email alerts
|

Association between PPAR-γ2 Pro12Ala genotype and insulin resistance is modified by circulating lipids in Mexican children

Abstract: The Pro12Ala (rs1801282) polymorphism in peroxisome proliferator-activated receptor-γ2 (PPAR-γ2) has been convincingly associated with insulin resistance (IR) and type 2 diabetes (T2D) among Europeans, in interaction with a high-fat diet. Mexico is disproportionally affected by obesity and T2D however, whether the Pro12Ala polymorphism is associated with early metabolic complications in this population is unknown. We assessed the association of PPAR-γ2 Pro12Ala with metabolic traits in 1457 Mexican children us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The Pro12Ala PPAR-γ2 G minor allele frequency in the literature ranges from 9% to 25% [9,[15][16][17]57,58]. In this study, the frequency in the total studied population was 17%, while other studies in Mexican population report 10-21% [11,17]. Similarly, the +294T/C PPAR-δ C minor allele frequencies vary from 12% to 31% among different populations [22,24,25,[27][28][29][30]35,[59][60][61].…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…The Pro12Ala PPAR-γ2 G minor allele frequency in the literature ranges from 9% to 25% [9,[15][16][17]57,58]. In this study, the frequency in the total studied population was 17%, while other studies in Mexican population report 10-21% [11,17]. Similarly, the +294T/C PPAR-δ C minor allele frequencies vary from 12% to 31% among different populations [22,24,25,[27][28][29][30]35,[59][60][61].…”
Section: Discussionmentioning
confidence: 42%
“…A few studies in Mexican teenagers have shown association with Pro12Ala PPAR-γ2 polymorphism with obesity-related traits. Stryjecki et al reported an association between this polymorphism with insulin resistance in Mexican children [11]. No studies about +294T/C PPAR δ polymorphism and metabolic traits in Mexican children were found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the data concerning Pparγ polymorphisms focus on the Pro(12)Ala substitution. Based on a report of a population of children in Mexico, Pro(12)Pro homozygosity is the more represented, followed by Pro(12)Ala heterozygosity, and more rarely Ala(12)Ala homozygosity (73.9%:24.5%:1.6%) [ 705 ]. The (12)Ala PPARγ protein shows a decreased binding affinity for PPRE and consequently is a weaker stimulator of target gene expression [ 441 , 706 ].…”
Section: Major Outcomes Of Crmentioning
confidence: 99%
“…Recently, a candidate gene approach study demonstrated that the Pro12Ala polymorphism in PPARG was associated with IR in Mexican children and suggested that this relationship was modified by dyslipidaemia. 19 Therefore, genetic studies of T2D in adults and epidemiological, as well as non-genetic (such as nutritional and physical activity), studies of IR and T2D in children are numerous, whereas genetic studies specifically aiming to identify novel genes predisposing to IR in children and adolescents are lacking.…”
Section: Introductionmentioning
confidence: 99%